Role of colchicine in the management of COVID-19 patients: A meta-analysis of cohort and randomized controlled trials - Avinash Kumar Singh; Arya Vidyadhari; Harmandeep Singh; Kashif Haider; Anoop Kumar; Manju Sharma (Elsevier, 2022)
Background: Colchicine is well known drug for the treatment of acute gout. Recently, it has also been used in the management of COVID-19 patients. Aim: The aim of current study is to find out the role of colchicine in COVID-19 patients. Material & methods: The relevant studies were searched in PubMed/Medline, Google scholar and clinical trail.gov.com till inception and sorted based on the inclusion and exclusion criteria. The quality assessment of studies were done using Newcastle Ottawa Quality Assessment Scale. The pooled estimate was calculated as odd ratio and pooled prevalence with 95% confidence interval. A random effect model was used and publication bias was assessed qualitatively by trim and fill method. Results: Out of 38 studies, a total of 6 studies were found relevant for the analysis containing 1146 patients (705 males and 441 females). The pooled odd ratio was found to be 0.35 [0.23, 0.53] which indicate significance reduction of mortality in colchicine group as compared to non-colchicine group. The pooled prevalence of the patients treated with colchicine were found to be significant [0.11(0.03, 0.24)]. The heterogeneity among studies was also found to be low (I2 = 11%). However, funnel plot has indicated the involvement of publication bias [Egger: bias = 10.168291 (95% CI = 5.042044 to 15.294537) P = 0.0053]. Conclusion: Colchicine might be helpful in reduction of mortality in the management of COVID-19 patients. However, further studies are required to confirm its exact role.